Análise da qualidade da informação no setor de saneamento básico: em busca da inteligência estratégica - CONDURÚ, Marise Teles (Universidade Federal do Pará, 2013)
This study talks about the informational dimension of the basic sanitation section, and has as objective to analyze the quality of the available information in sources of information used in the planning of the section. For that, the government bases of information were analyzed, the National System of Information on Sanitation 2009 (SNIS), the National Research of Basic Sanitation 2008 (PNSB), the National Research for Sample of Homes 2009 (PNAD) and the Demographic Census 2010, in the national ambit, and the Service of Information of the State of Pará 2009 (SIE). The analysis was accomplished through the Diagram of Pareto, the cause and effect Diagram of Ishikawa as well as the attributes of information as: up to date, inclusion, reliability, precision and pertinence, besides, the specialists' of the section opinion was investigated. In the 15 problems evidenced in the reduction of the quality of the information in basic sanitation, five of them are considered vital and they influence the other problems, as: the) interaction lack with other areas; b) inadequate periodicity of dissemination of the information; c) lack of detail of the information; d) inadequate forms of collection; e) inadequate information organization. Starting from the verification of the fragilities in the dimension informational in basic sanitation, the information was analyzed used in two instruments of planning of the section, the National Plan of Basic Sanitation (PLANSAB) and the Pluri Annual Plan of the state of Pará 2008/2011, (PPA 2008/2011). The conclusion of this thesis is that, in the moment, the information available for the planning of the section are out of to date, incomplete, imprecise, irrelevant and mistrust. Therefore, actions of strategic intelligence were recommended to improve the quality of the information of the section, being defined the what and where to collect, how to systematize, to analyze, to disseminate, to evaluate and to monitoring the information, seeking to contribute for the planning, definition of investments, installment of the services, regulation, inspection and social control, in agreement with the guidelines of the National Politics of Basic Sanitation, Law n. 11.445/2007, that has as one of the fundamental beginnings the universalization of the access to population to the services of basic sanitation.